Use of Aloe Vera Gel-Based Edible Coating with Natural Anti-Browning and Anti-Oxidant Additives to Improve Post-Harvest Quality of Fresh-Cut ‘Fuji’ Apple - Vittorio Farina; Roberta Passafiume; Ilenia Tinebra; Eristanna Palazzolo; Giuseppe Sortino (Agronomy, 2020)
Recently, there is increasing use of edible and biodegradable films and packaging that are both environmentally friendly and functional for storage and market distribution. Fresh-cut ‘Fuji’ apples, harvested in an organic farm, were treated, using a spraying technique, with three new edible coatings based on Aloe vera gel (AVG—40% v/w) and in combination with natural additives: lemon essential oil (LEO—1% v/w) and hydroxypropyl methylcellulose (HPMC—0.1% v/w) and compared with untreated sample (CTR), the physicochemical and sensory characteristics and the proximate compounds were evaluated. During cold storage, weight loss, soluble solids content, and color of uncoated slices were reduced, while softening, ripening, browning, and acidity were accelerated. In contrast, the AVG/HPMC treatment significantly delayed the above parameters related to post-harvest quality loss, while the AVG/LEO treatment delayed the browning processes, maintaining an excellent color during cold storage. Concerning proximate compounds, the treatments did not alter their concentration in the fruit tissues. Sensory analyses revealed no detrimental effect on taste, aroma, or flavor. Our data evidenced the positive effect of Aloe vera gel in combination with LEO and HPMC on fresh-cut apple quality as an innovative and sustainable technique to maintain fresh-cut apple quality.